Ireland in a Danish mirror: A microlevel comparison of the productivity of Danish and Irish creameries before the First World War - Eoin McLaughlin; Paul Sharp; Xanthi Tsoukli; Christian Vedel (European Historical Economics Society (EHES), 2021)
The relative success of the Danish and failure of the Irish dairy industries before the First World War is often contrasted given their competition for the lucrative British butter market. The traditional narrative implicitly assumes that Ireland failed because it was unsuccessful at adopting the cooperative institution, and that Irish cooperatives were not as efficient as their Danish counterparts, despite having been explicitly modelled on them. This assumption is, however, untested at the 'firm' level. We seek to rectify this through the analysis of a large microlevel database of creameries in both countries over the period 1898-1903. Using Stochastic Frontier Analysis (SFA), a standard methodology in modern productivity studies, we find no evidence for significant productivity differences on average, although there was a much larger variance in Ireland. This nuances the idea that the Irish were unable to cooperate successfully, although some creameries were certainly productivity laggards.
Keywords: N13; N53; 330; Dairying; Denmark; Ireland; microdata; productivity